Hormonal contraceptive use and self-reported menstrual cycle-related symptom frequency and severity in Norwegian team handball players of different competition levels - Osborne, J; Andersson, E; Pedersen, S; Welde, B; Pettersen, S; Emaus, A; Solli, G; Gunnarshaug, T; Engseth, T. (International Journal of Sports Physiology and Performance, 2025)
Purpose: To compare the frequency and severity of self-perceived negative symptoms associated with the menstrual cycle or hormonal-contraceptive (HC) cycle between (1) HC users and non-HC users and (2) different competition levels. An additional aim was to describe the rate and type of HC use and prevalence of potential menstrual-cycle disturbances in female team handball players.